2021
DOI: 10.1186/s12889-021-10891-w
|View full text |Cite
|
Sign up to set email alerts
|

Emotional exhaustion in front-line healthcare workers during the COVID-19 pandemic in Wuhan, China: the effects of time pressure, social sharing and cognitive appraisal

Abstract: Background With the increasing spread of COVID-19, healthcare workers, especially front-line medical staff, have become more vulnerable to emotional exhaustion. Objectives This study aimed to determine the influence of time pressure on the emotional exhaustion of front-line healthcare workers, and explore the effects of social sharing and cognitive reappraisal on this. Methods This cross-sectional stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 23 publications
(30 reference statements)
3
27
0
Order By: Relevance
“…Recent reports [55,61,64,71] suggest that the mother's cognitive appraisal of the disaster has a stronger moderating effect than main effect, which would be consistent with the stress model of Lazarus and Folkman [18]. The moderating effect of cognitive appraisal has been reported in studies of maternal mental health during COVID [72,73]. For diet change, we were only able to test the effect with one type of outcome (birth outcomes) and that effect was significant.…”
Section: Discussionsupporting
confidence: 76%
“…Recent reports [55,61,64,71] suggest that the mother's cognitive appraisal of the disaster has a stronger moderating effect than main effect, which would be consistent with the stress model of Lazarus and Folkman [18]. The moderating effect of cognitive appraisal has been reported in studies of maternal mental health during COVID [72,73]. For diet change, we were only able to test the effect with one type of outcome (birth outcomes) and that effect was significant.…”
Section: Discussionsupporting
confidence: 76%
“…This is congruent with previous results who identified that being first-line worker as a risk factor for emotional difficulties ( 11 , 33 ). We can assume though that front-line workers have greater time pressure and workload, resulting in more important level of emotional difficulties ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies tried to understand and to conceptualize the psychological consequences of COVID-19 among healthcare workers. The first factors proposed to explain these emotional difficulties were increased time pressure and workload ( 20 ), as it increases work-life imbalance, known as a risk factor for burnout ( 21 ). Other authors have proposed that repeated stress could be the cause of burnout ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Negative physical issues were also discussed. Frontline nurses worked with heavy equipment and long shift‐time work during the COVID‐19 outbreak; they tended to presented burnout and emotional exhaustion (Wang et al, 2021 ; Zhang et al, 2020 ). A large sample and multicentre study reported that more than 50% frontier nurses suffered from insomnia during their frontline works (Zhan, Liu, et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%